IOC, IPC, Tokyo 2020 Organising Committee and Tokyo Metropolitan Government announce new dates for the Olympic and Paralympic Games Tokyo 2020 (2020)
The International Olympic Committee (IOC), the International Paralympic Committee (IPC), the Tokyo 2020 Organising Committee, the Tokyo Metropolitan Government and the Government of Japan today agreed new dates for the Games of the XXXII Olympiad, in 2021. The Olympic Games Tokyo 2020 will be celebrated from 23 July to 8 August 2021. They also agreed on new dates for the Paralympic Games, which will be celebrated from 24 August until 5 September 2021.